Music practice assessment by cultural arts teachers in Bengkayang junior high schools: A qualitative study - Imam Ghozali; Zakarias Aria Widyatama Putra; Chiristianly Yery Silaban; Vivi Ervina Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
There is a notable research gap regarding effective strategies for music practice learning among cultural arts teachers in junior high schools, particularly in Bengkayang. This study addresses the urgent need to enhance the quality of arts education by investigating innovative approaches in music practice instruction. Employing a qualitative research design, the population comprised all cultural arts teachers at junior high schools throughout Bengkayang Regency. Purposive sampling was used to select participants actively engaged in music practice teaching. Data were collected through in-depth interviews, observations, and document analysis, utilizing interview guides, observation sheets, and supporting documents as research instruments. The findings reveal that teachers face significant challenges, such as limited facilities and time constraints, yet demonstrate novelty in their adaptive strategies that leverage local wisdom—an aspect seldom explored in prior studies. It is explicitly recommended that schools and local authorities improve infrastructure, provide regular professional development, and formulate supportive policies to optimize music practice learning. These results are expected to inform both local and national policy development for contextual arts education.